Selection of housekeeping genes for real-time PCR in atopic human bronchial epithelial cells - He, J.Q.; Sandford, A.J.; Wang, I.M.; Stepaniants, S.; Knight, D.A.; Kicic, Anthony; Stick, S.M.; Paré, P.D. (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2008)
The stability of housekeeping genes (HKGs) is critical when performing real-time quantitative PCR. To date, the stability of common HKGs has not been systematically compared in human airway epithelial cells (AEC) in normal and atopic subjects. Expression levels of 12 HKGs were measured in AECs from a cohort of 30 healthy atopic nonasthmatic or atopic asthmatic children. Gene expression stability was determined using three different Visual Basic for Applications applets (geNorm, NormFinder and BestKeeper). All 12 HKGs were expressed in AECs. However, the hypoxanthine ribosyltransferase and TATA-binding protein genes were excluded from further analysis due to low expression levels. The cyclophilin A gene was ranked the most stable by all three methods. The expression levels of the β-actin and glyceraldehyde-3-phosphate dehydrogenase genes were significantly different between the three groups of patients, with atopic asthmatics showing the highest expression levels for both genes. The results suggest that the cyclophilin A gene is the most suitable housekeeping gene analysed for expression studies utilising uncultured bronchial airway epithelial cells from healthy and asthmatic children, and highlight the importance of validating housekeeping genes for each experimental model. Copyright©ERS Journals Ltd 2008.